Willingness-to-pay and parametric trends in cost-effectiveness and cost-utility studies in ophthalmology - Tina Felfeli; Rafael N Miranda; Aswen Sriranganathan (BMJ Open Ophthalmology)
Objective To evaluate the frequencies of input parameters in cost-effectiveness analyses (CEA) within ophthalmology, particularly in willingness-to-pay (WTP), and to assess trends over time in studies conducted in the United States.Methods and analysis A cross-sectional analysis of CEAs from the Tufts Medical Center CEA Registry spanning 1993 to 2022 was conducted, including all studies evaluating diseases of the eye and adnexa. The primary outcomes measured included trends in WTP thresholds, funding sources, types of interventions and disease classifications.Results A total of 82 US-based CEAs met the inclusion criteria. All studies assessed outcomes in quality-adjusted life years (QALYs). WTP thresholds of US$50 000 (41%) and US$100 000 (39%) were most frequently reported, with US$150 000 emerging in 9% of studies since 2019. Discounting at 3.0% for costs and QALYs was universally applied. Government (33%), nonprofit (29%) and pharmaceutical (17%) funding predominated. Pharmaceutical-funded studies often employed higher WTP thresholds of US$100 000 (29%) and US$150 000 (29%). The most common intervention types were surgical (40%) and pharmaceutical (40%), whereas diseases of the choroid and retina (43%) were most frequently studied. Healthcare perspectives (17 studies) were more commonly reported than societal perspectives (6 studies).Conclusions US-based ophthalmology CEAs commonly use US$50 000–$100 000 WTP thresholds and a 3.0% discount rate, with higher thresholds emerging recently. Public and nonprofit funding predominates, focusing on retinal diseases and surgical or pharmaceutical interventions. Reassessing fixed WTP thresholds and incorporating societal perspectives could improve CEAs’ relevance, ensuring alignment with evolving economic and healthcare landscapes.